Data Driven: Harnessing Data and AI to Reinvent Customer Engagement (getAbstract Summary). - , getAbstract (linkedin.com, 2019)
Learn how technology can support marketing in the digital era, in this audio-only summary of the popular book by Tom Chavez, Vivek Vaidya, and Chris O’Hara.